Improved corrosion resistance of TiAlCrNbMo alloy to lead-bismuth eutectic by pre-oxidation - Y. Liu; H.E. Ge; Q.S. Ren; H.W. Deng; Z. Li; B. Du; T. Zhang (Journal of Materials Research and Technology, 2024)
A Ti48.5Al46Cr3Nb0.5Mo2 alloy was designed and fabricated to investigate its corrosion resistance to static liquid lead-bismuth eutectic (LBE). The microstructure and corrosion behavior of un-oxidized and pre-oxidized samples were compared. The results show that LBE preferentially penetrated into the alloy along the CrMo-rich σ phase formed at high-temperature. A TiO2 and Al2O3 oxide layer was formed on the surface of the matrix after 2 h pre-oxidized leading to remarkable LBE resistance. When extended the pre-oxidized time to 4 h, the exfoliation of the oxide layer caused by the evaporation of MoO3 significantly weakens the corrosion resistance.